Individual- and system-level determinants of breastfeeding in a low-resource setting - Loutet, Miranda G. (Frontiers in Public Health, 2024)
The benefits of breastfeeding are widely established and therefore the World Health Organization recommends that every child be exclusively breastfed for the first 6 months of life and continue breastfeeding up to 2 years of age or beyond. However, the rate of exclusive breastfeeding is low globally and has declined in Bangladesh in recent years. In this review, Bangladesh is used as an example to demonstrate the complex individual- and system-level determinants of breastfeeding in a low-resource setting. Mothers face barriers to breastfeeding within the context of marketing by commercial milk formula companies, limited safe alternatives to breastfeeding directly from the breast, and insufficient resources to support breastfeeding in the hospital, community, and workplace setting. Future research and implementation science is required to investigate the overlapping effects between breastfeeding and the high antibiotic use and Caesarean section rates in Bangladesh, along with public health efforts to promote breastfeeding based on robust evidence.